2019
DOI: 10.3390/agronomy10010047
|View full text |Cite
|
Sign up to set email alerts
|

Anther Extrusion and Its Association with Fusarium Head Blight in CIMMYT Wheat Germplasm

Abstract: Pronounced anther extrusion (AE) is associated with field resistance to Fusarium head blight (FHB), one of the most devastating diseases of wheat globally. In this study, two recombinant inbred line (RIL) populations were used to map quantitative trait loci (QTL) for AE and field FHB resistance and to investigate the association of both traits at the genetic level. Furthermore, two panels of International Maize and Wheat Improvement Center (CIMMYT) wheat breeding lines were evaluated to describe the phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…"Spark, " FHB resistance was largely conferred by the wild allele of the Rht-D1 gene, while the Rht-D1b allele found in the susceptible lines was responsible for approximately 50% of the phenotypic variance associated with the magnitude of initial infection (Srinivasachary et al, 2009). A similar increase of FHB infection has been described for the two particular alleles of the vernalizationrelated genes Vrn-A1 and Vrn-B1 (Xu et al, 2020). An FHB susceptibility source has also been identified in the "Sumai 3" Qfhs.kibr-2DS QTL (Figure 1), in which a specific allele encoding a multidrug resistance-associated protein was identified in the susceptible "Sumai 3"-derived cv.…”
Section: Genetics Demonstration Of the Existence Of Wheat Susceptibilmentioning
confidence: 69%
“…"Spark, " FHB resistance was largely conferred by the wild allele of the Rht-D1 gene, while the Rht-D1b allele found in the susceptible lines was responsible for approximately 50% of the phenotypic variance associated with the magnitude of initial infection (Srinivasachary et al, 2009). A similar increase of FHB infection has been described for the two particular alleles of the vernalizationrelated genes Vrn-A1 and Vrn-B1 (Xu et al, 2020). An FHB susceptibility source has also been identified in the "Sumai 3" Qfhs.kibr-2DS QTL (Figure 1), in which a specific allele encoding a multidrug resistance-associated protein was identified in the susceptible "Sumai 3"-derived cv.…”
Section: Genetics Demonstration Of the Existence Of Wheat Susceptibilmentioning
confidence: 69%
“…S2), and this genetic linkage might have contributed to the phenotypic correlation. Apart from this QTL, none of the remaining QTL was associated with PH, being markedly different from those for FHB (He et al 2016 ; Xu et al 2020 ). This might also imply that PH has less impact on WB than on FHB, but further study is needed to corroborate or negate it.…”
Section: Discussionmentioning
confidence: 90%
“…Numerous studies have previously demonstrated that semi-dwarf Rht1 alleles are associated with FHB susceptibility (Srinivasachary et al, 2008(Srinivasachary et al, , 2009Lu et al, 2013;Buerstmayr and Buerstmayr, 2016;Prat et al, 2017), with the wild-type alleles Rht-B1a and Rht-D1a contributing to FHB resistance. Rht-B1 may contribute to resistance directly through the control of the plant height and flower microclimate through pleiotropy, hormone signaling, and modulation of flowering, anther retention and spike traits, or even through linkage drag (McCartney et al, 2007;Yan et al, 2011;Buerstmayr and Buerstmayr, 2016;Davière and Achard, 2016;He et al, 2016;Herter et al, 2018;Xu et al, 2020). The present study found that when the effect of plant height on FHB resistance caused by different disease pressure was controlled through the use of spray inoculation at Carman, the 4BS locus still had a large effect on FHB resistance, though the effect was reduced compared to the site using the spawn approach.…”
Section: Genetic Architecture Of Fhb Resistance Components and Their mentioning
confidence: 99%